English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

f(x)= 5x^2 at x= -1

5(1-h)^2 = 5-2h+h^2
=f'(-1)=lim(h-0)= 5-2h+h^2-5/h
=f'(-1)=lim(h-0)= h(-2+h)/h
=-2

The answer is actually -10...what did I do wrong??
Thank you..

2007-10-23 08:39:43 · 5 answers · asked by Caramel 2 in Science & Mathematics Mathematics

5 answers

Well, your first error is that you should have computed f(x+h), not f(-x-h). Otherwise, you'll get the derivative of f(-x) at x = -(-1) = 1. Your second error is that you forgot to distribute the 5 over the entire quantity in the parentheses. 5(-1+h)² = 5(1 - 2h + h²) = 5 - 10h + 5h². Now, computing this correctly, we see that:

f'(-1) = [h→0]lim (5(-1+h)² - 5)/h
f'(-1) = [h→0]lim (5 - 10h + 5h² - 5)/h
f'(-1) = [h→0]lim (-10h + 5h²)/h
f'(-1) = [h→0]lim -10 + 5h
f'(-1) = -10

As your answer key states.

2007-10-23 08:49:02 · answer #1 · answered by Pascal 7 · 2 0

Evaluated the expression at x=1 and not x= -1?

Also, 5(-1-h)^2 = 5 + 10h + 5h^2

2007-10-23 15:45:44 · answer #2 · answered by supastremph 6 · 0 0

5(-1+ h)^2 = 5(1 -2h + h^2) = 5 -10h + 5h^2

2007-10-23 15:47:00 · answer #3 · answered by Linda K 5 · 3 0

What are you trying to find?
lim at x = -1, or f(-1)
in this case, both are 5
Where you getting -10 from?

2007-10-23 15:56:41 · answer #4 · answered by 1294 4 · 0 0

f'(-1) = [h→0]lim (5(-1+h)² - 5)/h
f'(-1) = [h→0]lim (5 - 10h + 5h² - 5)/h
f'(-1) = [h→0]lim (-10h + 5h²)/h
f'(-1) = [h→0]lim -10 + 5h
f'(-1) = -10

2007-10-23 16:02:29 · answer #5 · answered by jewel7962002 1 · 0 0

fedest.com, questions and answers